The first case of canine visceral leishmaniasis in the southern region of Santa Catarina, an emerging focus of visceral leishmaniasis in Brazil: regional report or reflection of the reality of a country? (Research, Society and Development, 2021)
Visceral leishmaniasis is among the most neglected diseases in the world and especially affects poor populations of some developing or underdeveloped countries, with human disease being a factor in the occurrence of thousands of deaths every year. Visceral leishmaniasis affect domestic dogs, main reservoirs of the Leishmania parasite in urban environments. Thus, the aim of this study was to analyze the prevalence of canine visceral leishmaniasis in two non-endemic municipalities located in southern Santa Catarina, as well as to identify the main risk factors for infection in dogs. A cross-sectional study was carried out with dogs living in two Zoonoses Control Centers located in the cities of Tubarão and Criciúma. Blood samples were collected and analyzed by real-time PCR for detection of Leishmania infection. Clinical examination and evaluation of the characteristics of the canine population were also carried out. A total of 107 dogs were evaluated, of which 19% were positive for Leishmania, and 85% of the positive cases were asymptomatic. In conclusion, we highlight the detection of cases of canine visceral leishmaniasis in two cities that had not yet reported cases. The high rate of positive asymptomatic animals suggests the maintenance of the parasite in the environment.